Dinamika Eksistensi Peradilan Agama di Indonesia: Religious Courts - Warisni, Rinrin (Jurnal At-Tadbir : Media Hukum dan Pendidikan, 2021)
Abstarction: The dynamics of the existence of the Religious Courts in Indonesia for 139 years experienced ups and downs and ups and downs. Being able to survive for more than a century is not without a struggle process. Achieving glory during the Islamic Kingdom, experiencing adversity due to acculturation during the colonial period and re-established its existence after Indonesian independence. In fact, this long history has led the Face of the Indonesian Religious Courts to become one of the courts that are able to take part in the international world. Especially with the enactment of Law Number 7 of 1989 concerning Religious Courts. Keywords: Dynamics, Existence, Religious courts